2012
DOI: 10.3109/02688697.2012.685780
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and immunohistochemical expression levels of androgen, estrogen, progesterone and Ki-67 receptors in relationship with gross-total resected meningiomas relapse

Abstract: Our results demonstrate high recurrent rate for gross-total resection meningiomas. Tumour diameter exceeding 5 cm, irregular shape tumour, pathological grade II and III and positive expression of Ki-67 were the risk factors for post-operation meningioma relapse. The recurrent rate increases coincidentally with the follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…Various studies suggested that hormone levels, hormone receptor status, and chromosome abnormalities may affect the tendency for high-grade tumors. [21][22][23][24][25] Some studies have also shown an inverse relationship between progesterone receptor expression level and tumor histological grade and tumor recurrence. [22][23][24][25] The hormone-related molecules may be used as markers to identify low-grade and high-grade meningiomas.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies suggested that hormone levels, hormone receptor status, and chromosome abnormalities may affect the tendency for high-grade tumors. [21][22][23][24][25] Some studies have also shown an inverse relationship between progesterone receptor expression level and tumor histological grade and tumor recurrence. [22][23][24][25] The hormone-related molecules may be used as markers to identify low-grade and high-grade meningiomas.…”
Section: Discussionmentioning
confidence: 96%
“…In a metaanalysis evaluating Ki67 positivity in grade I meningiomas, the authors achieved average immunostaining of around 3% (range 1-16%), and around 4% (range 0-35%) in recurrent tumors (45). In other studies, meningiomas presenting Ki67 ≥ 3% also showed a greater tendency for recurrence (5,10,52,55,(59)(60)(61)(62)(63)(64). In contrast, some studies have not confirmed this trend based only on Ki67 (13,65,66).…”
Section: Cell Proliferation Index: Ki67mentioning
confidence: 90%
“…In this study, the median postoperative follow-up was 3.6 years, i.e., within the period that presents a higher number of recurrences. According to Tao et al (10), the higher the histological grade, Ki67, ER and AR, the higher the number of recurrences, and the finding was significant (p < 0.05). They also reported that grade I meningiomas have a recurrence risk of 7-20% after surgical resection, and this was significantly higher in meningiomas with high Ki67 (10), a finding also observed in our study.…”
Section: Cell Proliferation Index: Ki67mentioning
confidence: 93%
See 1 more Smart Citation
“…Among them are Estrogen Receptor (ER), Progesterone Receptor (PR), and Fibroblast Growth Factor Receptor 1 (FGFR1). 7,8 The relationship between DR to the incidence of Meningioma and its clinical profile were elucidated.…”
Section: Introductionmentioning
confidence: 99%